HOW TO CONTROL INTERDIALYTIC WEIGHT GAIN (IDWG) AMONG HEMODIALYSIS PATIENTS? - Lono Wijayanti; Priyo Mukti Pribadi Winoto; Nursalam Nursalam (Institute for Research and Community Service of Health Polytechnic of Kerta Cendekia, Sidoarjo, 2021)
Background: Chronic kidney failure is a terminal disease that often affects the patient's quality of life. One of the problems that often occurs in patients with end-stage renal failure is the increase in fluid volume between two dialysis times. The increase in Interdialytic Weight Gain (IDWG) has a serious impact, 60-80% of patients die from excess fluid and food intake during the interdialytic period. Objective: This review aimed to describe the importance of Interdialytic Weight Gain (IDWG) in end-stage renal failure patients undergoing hemodialysis. Design: This study design is a systematic review to search and review article from database and the theory underlying this study or guidance in this systematic literature review using PRISMA. Data Sources: This systematic review was conducted using a database with electronic searches on EBSCO, ProQuest, Scopus, SAGE, and Science Direct published in 2017-2021. Review Methods: The method used in the preparation of the Literature review using the PRISMA checklist and PICOT. Secondary data obtained from the journal with a predetermined discussion. Results: The results of the database search strategy were 1,907 articles were obtained, but 1,340 articles were excluded. There were seven articles that met the inclusion criteria. Two articles identified that uncontrolled IDWG is at risk of death in chronic renal failure patients undergoing hemodialysis. Conclusion: Two articles state that IDWG affects hemoglobin concentration and cardiovascular disorders and triggers complications, two other articles state that the factors that contribute to IDWG are fluid intake, thirst, self-efficacy and dietary behavior, one article states that controlled IDWG will improve the quality of life of patients with end-stage renal failure/End-Stage Renal Disease (ESRD undergoing hemodialysis. Uncontrolled IDWG is at risk of death in patients undergoing hemodialysis. Control of IDWG through adherence to dietary behavior will improve the quality of life of end-stage renal failure patients undergoing hemodialysis.